2007
DOI: 10.1002/pbc.20860
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the neurocognitive sequelae of treatment for childhood acute lymphocytic leukemia

Abstract: The results from this meta-analysis suggest that declines in both global and specific areas of areas of neurocognitive functioning occur as a result of contemporary ALL treatment. Such deficits have significant implications for survivors' academic achievement and overall quality of life. Neurocognitive assessment plays a critical role in determining what remedial or specialized instruction is needed in childhood ALL survivors and should be included as a standard part of long-term follow-up care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
213
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(232 citation statements)
references
References 38 publications
12
213
3
4
Order By: Relevance
“…Our findings are consistent with those of a recently published study that found over 90% of Latino parents of childhood cancer survivors expressed interest in a culturally competent intervention aimed at reducing neurocognitive late effects [9]. Our intervention is based on the premise that neurocognitive assessment should be a standard component of survivorship care for at-risk patients, and that it plays a crucial role in addressing immediate school needs, as well as longer-term educational, vocational, and employment outcomes [2][3][4]10]. We believe that the critical ingredient of our approach is its culturally competent design and implementation (Table S1), which includes a culturally and linguistically competent psychologist.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings are consistent with those of a recently published study that found over 90% of Latino parents of childhood cancer survivors expressed interest in a culturally competent intervention aimed at reducing neurocognitive late effects [9]. Our intervention is based on the premise that neurocognitive assessment should be a standard component of survivorship care for at-risk patients, and that it plays a crucial role in addressing immediate school needs, as well as longer-term educational, vocational, and employment outcomes [2][3][4]10]. We believe that the critical ingredient of our approach is its culturally competent design and implementation (Table S1), which includes a culturally and linguistically competent psychologist.…”
Section: Discussionsupporting
confidence: 87%
“…Although approximately 90% of patients become long-term survivors, up to 40% may develop treatment-related neurocognitive dysfunction that impairs learning and school performance [1][2][3]. Consequently, routine neuropsychological screening is recommended by the Children's Oncology Group (COG Long-Term Follow-Up Guidelines) for all childhood ALL survivors [4].…”
Section: Introductionmentioning
confidence: 99%
“…The relation between special education programs and achievement among survivors (other than survivors of CNS tumors or leukemia) needs to be explored further to address the question of the contribution of special education to achievement in this group. Finally, although studies consistently have indicated that survivors experience adverse neurocognitive late effects, [18][19][20][21]50 these need to be linked clearly to poor achievement in school 60 and educational intervention opportunities. 61 …”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Survivors attain lower levels of education, [9][10][11][12] have increased use of special education services, [13][14][15][16] and have a greater likelihood of grade repetition. 13,17 There is considerable evidence of adverse neurocognitive late effects, [18][19][20][21] including lower intelligence quotient scores, 22,23 that may inhibit educational performance.…”
mentioning
confidence: 99%
“…[13][14][15] Individual studies in the past have shown some negative effects of treatment. However, most of these studies were hindered by small sample size and lack of appropriate controls, which makes it challenging to interpret and generalize their findings.11-14 Conclusions from systematic reviews have been mixed, [16][17][18] largely because of reliance on qualitative methods to assess outcomes 18 and inclusion of studies with patients who had very recently completed therapy or without a control population. [16][17][18] Because neurocognitive impairment takes time to develop and/or be detected, early assessments are likely not adequate.…”
mentioning
confidence: 99%